Assessing the transforming power of social innovation through the perceptions of its beneficiaries - Sousa, C.; Ferreiro, Maria de Fátima (16th European Conference on Innovation and Entrepreneurship, 2021)
This paper tackles a still underexplored topic in the literature on social innovation - the assessment of its impacts, drawing on the concept of transformative social innovation. This concept stresses the changes in social relations and in dominant institutions and the emergence and dissemination of new knowledge and new practices linked to the emergence and deployment of social innovations. The empirical research considers the beneficiaries of a social innovation project - the EPAM project and uses primary data, collected through a questionnaire. The results show the beneficiaries’ assessment of the impacts of this SI project on their activities, namely those relate to the development of their businesses and new partnerships, as well as to the access to new knowledge.